CSR, organizational identification, normative commitment, and the moderating effect of the importance of CSR - El-Kassar, Abdul-Nasser (2017)
Commitment results from an assessment of situations found at the work place linking employees to their organization, and their effort towards achieving goals. Corporate Social Responsibility (CSR) is management's obligation, not solely to maximize economic profit, but also represent humanitarian social causes. CSR has been linked employee organizational identification (EOI) and to commitment. This research examines the moderating effect of the perceived importance of corporate social responsibility (ICSR) on the relationships among CSR, EOI and commitment. The constructs were numerically measured and the model was analyzed using partial least square structural equation modeling. Cross-sectional data was collected through convenience sampling targeting employees working at different organizations within Lebanon (a country in the Middle East and North Africa region). 287 participants fully completed the survey. The questionnaire contains 15 items measuring CSR, 5 questions relating to EOI, 8 items measuring the normative commitment, a 5-item scale to measure the importance of ethics and social responsibility to employees, and demographics. Based on previous research, all scales used are valid and reliable.Empirical evidence indicate that employee identification mediate the relationship between CSR and normative commitment. Also, ICSR was found to moderate some of these relationships. These findings were obtained by first, demonstrating the reliability and validity of the measurement model, and then by calculating the structural model path coefficients and determining their significance. Also, cluster analysis was used to partition the respondents into two groups on the bases of whether or not they view CSR as important. Multi-group analysis was then conducted to determine the moderating effects of ICSR on the relationship between CSR, EOI, and normative commitment. In particular, significant effects were found between CSR towards customer, employees, and stakeholders on employee identification. Additionally, results show that employee identification moderates the relationship between the employees and stakeholders' components of CSR and normative commitments. It is recommended when formulating CSR initiatives, companies take into consideration what employees value and perceive as important, so that their company identification is enhanced leading to increased commitment. As such, companies ought to align their corporate values and interests with that of employees when determining CSR activities.